How the origins of international investment law are reflected in arbitration awards: a study on the 2001 Argentinean crisis - Moreira, Natali Francine Cinelli (2019)
International investment law is the product of power struggles between capital-exporting and capital-importing countries, whose origins may be traced back to imperial times. Investment treaties include old standards of investors\' protection under a new form and allegedly under a veil of depoliticization. This is what happened with the Fair and Equitable Treatment standard; the origins of this standard may be traced to the international minimum treatment of aliens, a well-known instrument that capital-exporters used to serve their expansionist intent during the 19th century. These standards are very extensive, and arbitrators have wide discretion when interpreting them. We argue that the imperial origins of international investment law influence arbitrators during decision-making, leading to a pervasive bias in the system in favor of investors and their home states. We use the 2001 Argentinean financial crisis as a case study, and we analyze all available awards rendered by investor-state tribunals in the context of this emergency period. We focus the analysis on the Fair and Equitable Treatment, for investors repeatedly invoked the breach of this standard and, in almost all cases, arbitrators used it to find Argentina responsible for the alleged damages. We found evidence that the imperial origins of investment law indeed influences decision-making. By replicating patterns of inequality and subjugation typical of imperial times, arbitrators inadequately favored investors. We thus have found evidence that the legal framework for the protection of international investment is not so impartial as it is claimed to be.